Climate change policies in 16 West African countries: a systematic review of adaptation with a focus on agriculture, food security, and nutrition - Sorgho, Raissa; Montenegro Quiñonez, Carlos Alberto; Louis, Valérie R.; Winkler, Volker; Dambach, Peter; Sauerborn, Rainer; Horstick, Olaf (International journal of environmental research and public health, 2020)
Climate change strongly impacts the agricultural sector in West Africa, threatening food security and nutrition, particularly for populations with the least adaptive capacity. Little is known about national climate change policies in the region. This systematic review identifies and analyses climate change policy documents in all 16 West African countries: (1) What are the existing climate change adaptation policies publicly available? (2) Which topics are addressed? (3) How are agriculture and food security framed and addressed? Following PRISMA guidelines, PubMed and Google scholar as key databases were searched with an extensive grey literature search. Keywords for searches were combinations of “Africa”, “Climate Change”, and “National Policy/Plan/Strategy/Guideline”. Fifteen countries have at least one national policy document on climate change in the frame of our study. Nineteen policy documents covered seven key sectors (energy, agriculture, water resources, health, forestry, infrastructure, and education), and eight thematic areas (community resilience, disaster risk management, institutional development, industry development, research and development, policy making, economic investment, and partnerships/collaboration). At the intersection of these sectors/areas, effects of changing climate on countries/populations were evaluated and described. Climate change adaptation strategies emerged including development of local risk/disaster plans, micro-financing and insurance schemes (public or private), green energy, and development of community groups/farmers organizations. No clear trend emerged when analysing the adaptation options, however, climate change adaptation in the agriculture sector was almost always included. Analysing agriculture, nutrition, and food security, seven agricultural challenges were identified: The small scale of West African farming, information gaps, missing infrastructure, poor financing, weak farmer/community organizations, a shifting agricultural calendar, and deteriorating environmental ecology. They reflect barriers to adaptation especially for small-scale subsistence farmers with increased climate change vulnerabilities. The study has shown that most West African countries have climate change policies. Nevertheless, key questions remain unanswered, and demand for further research, e.g., on evaluating the implementation in the respective countries, persists.
Gesehen am 19.02.2021